Peranan Aparat Penegak Hukum dan Lembaga Sosial dalam Penanganan Kasus KDRT di Pademangan Barat - Hendrawarman, Hendrawarman; Hidayat , Hendrik; Sari , Ratna; Munthe , Josua Epernando; Sopian, Mohamad Asep (Postulat, 2025)
Handling cases of Domestic Violence (DV) in Pademangan Barat is a complex challenge that requires synergistic collaboration between law enforcement officials and social institutions. Although established as a criminal offense through Law No. 23 of 2004, DV often goes unreported as it is considered a private matter or family disgrace, creating an "iceberg phenomenon". This study, conducted through a community service socialization activity in the Pademangan Barat sub-district, examines the roles of these two pillars. The results indicate that law enforcement officials play a fundamental role in the juridical process to provide a deterrent effect and justice , yet its effectiveness still faces challenges such as the "No Viral, No Justice" phenomenon. On the other hand, social institutions play a crucial complementary role focusing on the victim through three essential stages : Preventif, Respresif dan Kuratif.